An effective pedagogy for child welfare education. Issue 3 (27th May 2018) - Strand, Virginia C.; Popescu, Marciana
ABSTRACT: Preparing social workers for child welfare practice with the complexly traumatized children now in the system has created the need for schools of social work to integrate trauma content into the curriculum. This article presents findings of an evaluation of a child welfare course designed to prepare MSW level trauma-informed child welfare practitioners. Findings indicate that students in 29 schools of social work not only significantly increased their confidence in working with traumatized children and families but also are significantly more prepared to work toward these three child welfare goals of safety, permanency, and well-being.